Doxorubicin-conjugated beta-NaYF4:Gd3+/Tb3+ multifunctional, phosphor nanorods: a multimodal, luminescent, magnetic probe for simultaneous optical and magnetic resonance imaging and an excellent pH-triggered anti-cancer drug delivery nanovehicle - Padhye, Preeti; Alam, Aftab; Ghorai, Suvankar; Chattopadhyay, Sarnit; Poddar, Pankaj (Nanoscale, 2015)
Herein, we report the fabrication of a multifunctional nanoprobe based on highly monodispersed, optically and magnetically active, biocompatible, PEI-functionalized, highly crystalline beta-NaYF4:Gd3+/Tb3+ nanorods as an excellent multi-modal optical/magnetic imaging tool and a pH-triggered intracellular drug delivery nanovehicle. The static and dynamic photoluminescence spectroscopy showed the presence of sharp emission peaks, with long lifetimes (similar to 3.5 milliseconds), suitable for optical imaging. The static magnetic susceptibility measurements at room temperature showed a strong paramagnetic signal (chi similar to 3.8 x 10(-5) emu g(-1) Oe(-1)). The nuclear magnetic resonance (NMR) measurements showed fair T-1 relaxivity (r(1) = 1.14 s(-1) mM(-1)) and magnetic resonance imaging gave enhanced T-1-weighted MRI images with increased concentrations of beta-NaYF4:Gd3+/Tb3+ making them suitable for simultaneous magnetic resonance imaging. In addition, an anticancer drug, doxorubicin (DOX) was conjugated to the amine-functionalized beta-NaYF4:Gd3+/Tb3+ nanorods via pH-sensitive hydrazone bond linkages enabling them as a pH-triggered, site-specific drug delivery nanovehicle for DOX release inside tumor cells. A comparison between in vitro DOX release studies undertaken in normal physiological (pH 7.4) and acidic (pH 5.0) environments showed an enhanced DOX dissociation (similar to 80%) at pH 5.0. The multifunctional material was also applied as an optical probe to confirm the conjugation of DOX and to monitor DOX release via a fluorescence resonance energy transfer (FRET) mechanism. The DOX-conjugated beta-NaYF4:Gd3+/Tb3+ nanorods exhibited a cytotoxic effect on MCF-7 breast cancer cells and their uptake by MCF-7 cells was demonstrated using confocal laser scanning microscopy and flow cytometry. The comparative cellular uptakes of free DOX and DOX-conjugated beta-NaYF4:Gd3+/Tb3+ nanorods were studied in tumor microenvironment conditions (pH 6.5) using confocal imaging, which showed an increased uptake of DOX-conjugated beta-NaYF4:Gd3+/Tb3+ nanorods. Thus, DOX-conjugated beta-NaYF4:Get(3+)/Tb3+ nanorods combining pH-triggered drug delivery, efficient luminescence and paramagnetic properties are promising for a potential multifunctional platform for cancer therapy, biodetection, and optical and magnetic resonance imaging.

New imaging reagents for lipid dense regions in live cells and the nucleus in fixed MCF-7 cells - Ramu, Vadde; Ali, Firoj; Taye, Nandaraj; Garai, Bikash; Alam, Aftab; Chattopadhyay, Samit; Das, Amitava (Journal of Materials Chemistry B, 2015)
Two new uracil (U) and 5-flurouracil (5-FU) labeled ruthenium(II)-polypyridyl based cellular imaging reagents are reported. Confocal laser scanning microscopic images with live and paraformaldehyde (PFA) fixed MCF-7 cells are examined using these two low-cytotoxic reagents. Experimental results show that these two complexes, appropriately functionalized with U (1) and 5-FU (2), have specific affinity for the lipid dense regions like the endoplasmic reticulum, cell membrane, and cytoplasmic vacuoles in live MCF-7 cells, and dye internalization in these regions happened following an endocytosis pathway. Interestingly, these two complexes are found to be localized in the nucleus of the PFA fixed cells. For fixed cells, presumably the lipid layer disruption helped in the explicit localization of the complexes 1 and 2 in the cell nucleus through specific interaction with cellular DNA. Poor and non-specific internalization of an analogous model complex 3, without having a U or 5-FU moiety, reveals the definite influence of U or 5-FU as well as the role of lipophilicity of the respective complex 1 and 2 in the cellular internalization process. Apart from these, a large Stokes shift (similar to 160 nm) and an appreciably long lived (MLCT)-M-3 excited state (similar to 320 ns) in aq. buffer medium (pH 7.4) are other key features for complexes 1 and 2. Unlike the common nuclear DNA staining reagents like DAPI, these low-cytotoxic reagents are found to be highly stable towards photo-bleaching upon irradiation with 455 nm at the MLCT band for these complexes.

Oxidant mediated one-step complete conversion of multi-walled carbon nanotubes to graphene quantum dots and their bioactivity against mammalian and bacterial cells - Biswas, Anupam; Khandelwal, Puneet; Das, Raja; Salunke, Gayatri; Alam, Aftab; Ghorai, Suvankar; Chattopadhyay, Samit; Poddar, Pankaj (Journal of Materials Chemistry B, 2017)
It is essential for any antibacterial agent (for clinical applications) that it should have high and selective toxicity towards bacterial cells only, and should not affect the human cells at the concentration used. Graphene quantum dots (GQDs) have emerged as a potential candidate for biomedical applications. However, a simple, low cost, safe, easy to execute, one-step synthesis of uniform and monodispersed GQDs with selective toxicity towards bacterial cells rather than mammalian cells is difficult to achieve. Herein, we have reported a one-step, low-cost, aqueous-phase, simple approach for the complete conversion of multi-walled carbon nanotubes into water-dispersible GQDs with an average size of similar to 3 nm using sodium bismuthate (NaBiO3) as a strong oxidant. The cyclic voltammetry and X-ray photoelectron spectroscopy results indicated that the as-synthesized GQDs suspension possess almost negligible amounts of metallic impurities. The cytotoxicity studies of GQDs against mammalian NIH 3T3 (mouse embryo fibroblast cells) and HEK 293T (human embryonic kidney cells) cells showed that the as-synthesized GQDs were non-cytotoxic up to the concentration of similar to 200 mu g mL(-1). The antimicrobial study shows that the synthesized GQDs have high and selective toxicity towards bacterial cells with a minimum inhibitory concentration of similar to 256 mu g mL(-1) for E. coli and B. subtilis and similar to 512 mu g mL(-1) for P. aeruginosa and S. aureus. The scanning electron microscopy and atomic force microscopy images show extensive cell damage via the perturbation of bacterial cell walls, which was consistent with the enhancement of reactive oxygen species production by almost two times in the bacterial cells upon incubation with similar to 256 mu g mL(-1) GQDs. Our study suggested that the as-synthesized GQDs can be used as a potential candidate for clinical applications as they possess high toxicity to bacterial cells and low toxicity to mammalian cells.

Retention of anticancer activity of curcumin after conjugation with fluorescent gold quantum clusters: an in vitro and in vivo xenograft study - Khandelwal, Puneet; Alam, Aftab; Choksi, Arpankumar; Chattopadhyay, Samit; Poddar, Pankaj (ACS Omega, 2018)
Gold nanoparticles (Au NPs) have been thoroughly investigated for anti-cancer therapy. However, their undesired high gold content remains a problem when injected into the body for drug delivery applications. In this report, we made an effort to conjugate the curcumin molecules on the surface of gold quantum clusters (Au QCs) by a novel in situ synthesis method which provides an alternative route to not only reduce the metallic content but also increase the water solubility of curcumin and the loading efficiency. Here, curcumin itself acts as a reducing and capping agent for the synthesis of Au QCs. The UV−vis absorption, fluorescence, transmission electron microscopy, and electrospray ionization mass spectrometry results confirmed the synthesis of fluorescent Au QCs. Curcumin-conjugated Au NPs (C-Au NPs) and glutathione (GSH)-conjugated Au QCs (GSH-Au QCs) were also synthesized to visualize the effect of particle size and the capping agent, respectively, on the cytotoxicity to normal and cancer cells. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay showed that the curcumin-conjugated Au QCs (C-Au QCs) were less cytotoxic to normal cells while almost the same cytotoxic to cancer cells in comparison to curcumin itself, which indicates that curcumin preserves its anticancer property even after binding to the Au QCs. However, C-Au NPs and GSH-Au QCs did not show any cytotoxicity against the normal and cancer cells at the concentration used. The western blot assay indicated that C-Au QCs promote apoptosis in cancer cells. Further, the in vivo study on severe combined immunodeficiency mice showed that C-Au QCs also inhibited the tumor growth efficiently without showing significant toxicity to internal organs.